Reducing Employee Turnover Intention through Compensation, Support, and Engagement in Indonesia: Mengurangi Niat Keluar Masuk Karyawan melalui Kompensasi, Dukungan, dan Keterlibatan di Indonesia - Sahid, Ahmad; Firdaus, Vera (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the impact of compensation, organizational support, and work engagement on turnover intention at PT. Nugraha Ekakurir Line (JNE) Sidoarjo. Using a quantitative, descriptive method, data was collected via questionnaires from 114 respondents and analyzed with SPSS version 26. The results show that compensation, organizational support, and work engagement each have a negative and significant partial effect on turnover intention, and together they have a significant simultaneous effect. These findings suggest that enhancing compensation, organizational support, and work engagement can effectively reduce employee turnover. Highlight: Compensation, organizational support reduce turnover intention. Data from 114 respondents analyzed using SPSS 26. Enhancing these factors minimizes employee turnover. Keywoard: Compensation, Organizational Support, Work Engagement, Turnover Intention, Quantitative Study